1987
DOI: 10.1055/s-0038-1651126
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Decreases the High Plasminogen Activator Inhibition Capacity, Plasma Insulin and Triglyceride Levels in Non-Diabetic Obese Subjects

Abstract: SummaryWe have previously observed a positive correlation between Plasminogen Activator Inhibition capacity (PA Inhibition), Body Mass Index (BMI) and plasma insulin levels in a population of non diabetic subjects. The anti diabetic biguanide Metformin which decreases insulin resistance has been reported to increase the blood fibrinolytic activity. Therefore we have studied the effect of Metformin on PA Inhibition levels in obese subjects with normal glucose tolerance. Eighteen obese women (O) (BMI: 31.4 ± 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(67 citation statements)
references
References 24 publications
6
56
1
4
Order By: Relevance
“…50 Furthermore, the dissimilar effects on fibrinolysis of imidapril and candesartan might depend on their different effects on insulin sensitivity, whose relationship with PAI-1 level, observed in crosssectional studies, has been confirmed by interventional studies aimed at reducing insulin resistance, which have demonstrated a parallel decrease in plasma insulin and PAI-1 levels. 45,46,54 In the present study, imidapril significantly increased insulin sensitivity, as assessed by euglycemic-hyperinsulinemic clamp, whereas candesartan did not. These findings, which are in agreement with previous observations by ourselves and other authors, 35,[55][56][57] besides providing another possible explanation for the different effects of the two drugs on the fibrinolytic balance, also suggest that mechanisms other than Ang II inhibition, such as the increase in endogenous kinins because of ACE inhibition, might be responsible for the observed different influences of imidapril and candesartan on insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 41%
“…50 Furthermore, the dissimilar effects on fibrinolysis of imidapril and candesartan might depend on their different effects on insulin sensitivity, whose relationship with PAI-1 level, observed in crosssectional studies, has been confirmed by interventional studies aimed at reducing insulin resistance, which have demonstrated a parallel decrease in plasma insulin and PAI-1 levels. 45,46,54 In the present study, imidapril significantly increased insulin sensitivity, as assessed by euglycemic-hyperinsulinemic clamp, whereas candesartan did not. These findings, which are in agreement with previous observations by ourselves and other authors, 35,[55][56][57] besides providing another possible explanation for the different effects of the two drugs on the fibrinolytic balance, also suggest that mechanisms other than Ang II inhibition, such as the increase in endogenous kinins because of ACE inhibition, might be responsible for the observed different influences of imidapril and candesartan on insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, metformin improves fibrinolysis in cardiovascular disease ( 14). We have also shown in a previous study that, in obese non diabetic women, recovery of fibrinolytic activity after Metformin treatment was mainly due to decreased PAI-1 levels ( 15 ).…”
Section: Introductionmentioning
confidence: 69%
“…A strong positive association between PAI-1 activity and fasting insulin has been demonstrated in normal subjects, obese women and type 2 diabetic patients [16,25]. This relation is independent of body mass [16] and probably reflects insulin stimulated hepatic PAI-1 production [26].…”
Section: Discussionmentioning
confidence: 91%